Preparation of Galla Chinensis Oral Solution as well as Its Stability, Safety, and Antidiarrheal Activity Evaluation. (25th July 2017) - Yang, Yi; Luo, Huihui; Song, Xu; Yu, Li; Xie, Juan; Yang, Jiajie; Jia, Renyong; Lin, Juchun; Zou, Yuanfeng; Li, Lixia; Yin, Lizi; He, Changliang; et al.
Abstract : Background of the Study . As a widely used traditional medicine, Galla Chinensis is rich in tannins. However, there are few detailed studies about pharmaceutical preparations of Galla Chinensis tannin extract (GTE). In the present experiments, for better application and to investigate the possibility that Galla Chinensis tannin extract can be used as an antidiarrheal drug, we prepared Galla Chinensis oral solution (GOS). Materials and Methods . GOS was prepared with GTE, and its physicochemical and microbiological stability was evaluated. The oral acute toxicity of GOS was calculated by the 50% lethal dose (LD50 ). The antidiarrheal activity was determined in a castor oil-induced diarrhea model in mice through diarrhea symptoms, fluid accumulation ratio, and percentage of distance moved by charcoal meal. Results. The tannin content of GTE was 47.75%. GOS could endure a high temperature without a significant decrease of tannin content. After storage for six months, the tannin content of GOS was still more than 90%. GOS was determined to be nontoxic. Meanwhile, GOS showed significant antidiarrheal activity in a castor oil-induced diarrhea model in mice (P < 0.01 ). Conclusion . The results suggested that GOS is an effective and stable antidiarrheal drug that can be used to complement other therapies.